High Quantum Efficiency and High Concentration Erbium-Doped Silica Glasses Fabricated by Sintering Nanoporous Glasses - 达宁 乔延波 杨旅云 彭明营 汪晨 周秦岭 赵崇军 邱建荣 朱从善 陈丹平 赤井智子 (Journal of rare earths, 2006)
A new method was used to prepare erbium-doped high silica （SiO2 % 〉 96 % ） glasses by sintering nanoporous glasses. The concentration of erbium ions in high silica glasses can be considerably more than that in silica glasses prepared by using conventional methods. The fluorescence of 1532 nm has an FWHM （Full Wave at Half Maximum） of 50 nm, wider than 35 nm of EDSFA （erbium-doped silica fiber amplifer）, and hence the glass possesses potential application in broadband fiber amplifiers. The Judd-Ofelt theoretical analysis reflects that the quantum efficiency of this erbium-doped glass is about 0.78, although the erbium concentration in this glass （6 × 10^3） is about twenty times higher than that in silica glass. These excellent characteristics of Er-doped high silica glass will be conducive to its usage in optical amplifiers and microchip lasers.